2019
DOI: 10.3390/jcm8091453
|View full text |Cite
|
Sign up to set email alerts
|

The Neutrophil/Lymphocyte Count Ratio Predicts Mortality in Severe Traumatic Brain Injury Patients

Abstract: Introduction: Neutrophil-lymphocyte count ratio (NLCR) is a simple and low-cost marker of inflammatory response. NLCR has shown to be a sensitive marker of clinical severity in inflammatory-related tissue injury, and high value of NLCR is associated with poor outcome in traumatic brain injured (TBI) patients. The purpose of this study was to retrospectively analyze NLCR and its association with outcome in a cohort of TBI patients in relation to the type of brain injury. Methods: Adult patients admitted for iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 53 publications
3
48
2
Order By: Relevance
“…This study found that men were more likely to had a TBI compared to women. It supported several previous studies, which found that men had a bigger proportion compared to women in experiencing TBI, reaching 77-88% of TBI cases [29], [30], [34], [35], [36], [37]. The high incidence of TBI in men can be due to the fact that men are more dominant in doing high-risk activities, experiencing work-related accidents, and experiencing assaultrelated injuries compared to women [38].…”
Section: Samples Characteristicssupporting
confidence: 88%
“…This study found that men were more likely to had a TBI compared to women. It supported several previous studies, which found that men had a bigger proportion compared to women in experiencing TBI, reaching 77-88% of TBI cases [29], [30], [34], [35], [36], [37]. The high incidence of TBI in men can be due to the fact that men are more dominant in doing high-risk activities, experiencing work-related accidents, and experiencing assaultrelated injuries compared to women [38].…”
Section: Samples Characteristicssupporting
confidence: 88%
“…The neutrophil-lymphocyte ratio (NLR) has been widely proved to be a simple and reliable marker for assessing systemic inflammation and prognosis in non-traumatic and traumatic patients [1, [18][19][20][21][22][23]. In our study, we validated the predicted value of NLR (D3) and NLR (D7) using ROC curve given their differences between each two groups (Fig.…”
Section: Predictive Valuementioning
confidence: 89%
“…The acute in ammation phase of foreign body reaction against biomaterials is characterized by migration, adhesion, activation of neutrophils and mast cells, and lasts for hours to few days 27 . Just as the process of brain injury 28 , neutrophils' number increase greatly in the peripheral blood and they can enter central nervous system through the damaged blood brain barrier early 11 . Recruitment and in ltration of neutrophils around catheter could induce neurotoxicity by following pathways: production of cytotoxic mediators and proin ammatory cytokines, activation of matrix metalloproteinases and increase of oxidate stress [29][30][31] .…”
Section: Discussionmentioning
confidence: 99%
“…We hereby assume that in ammatory response is one of the mechanisms associated with DICH following VP shunt. The neutrophil-to-lymphocyte ratio(NLR), as a rapid and economic biomarker of systemic in ammation 9 , has been a dependable predictor of clinical outcome in patients with spontaneous intracerebral hemorrhage 10 and traumatic brain injury 11 .…”
Section: Introductionmentioning
confidence: 99%